Analisis Kesulitan Siswa dalam Pemecahan Masalah Matematika Materi Pecahan Kelas V SDN 2 Paokmotong Tahun Ajaran 2025/2026 - Yenika Fitri; Muhammad Turmuzi; Baiq Yuni Wahyuningsih; Nurkhaerat Alimuddin (Mataram University, 2026)
Problem-solving skills have become a key focus in mathematics education today. In mathematics class, students often face difficulties in solving non-routine problems or complex questions. This study aims to describe students’ difficulties in solving math problems involving fractions. This study employs a qualitative, descriptive research approach. The subjects of this study were 25 fifth-grade students at SDN 2 Paokmotong. The subjects were selected through purposive sampling, with three subjects chosen based on high, moderate, and low problem-solving ability categories. The data collection techniques used were a mathematics problem-solving test, interviews, and documentation. The data analysis techniques in this study included data collection, data reduction, data presentation, and drawing conclusions. Meanwhile, the validity of the research data was tested using triangulation. The results of the study show that: 1) subjects in the high category experienced difficulties at the stage of implementing their problem-solving plans; 2) subjects in the moderate category experienced difficulties at the stages of planning the solution, implementing the solution plan, and checking their work; and 3) subjects in the low category experienced the most difficulties, namely difficulties in understanding the problem because they were unable to identify the given information in the problem. Difficulties in the planning stage for problems 1 and 4 stemmed from an inability to create an accurate mathematical model. Difficulties in the execution stage resulted from not knowing how to apply formulas or not having memorized them. Difficulties in the review stage arose from an inability to solve the problems correctly.